Comparative advantages and factors affecting agriculture production and income in the food estate area on the Indonesia–Timor-Leste border - Taena, Werenfridus; Sipayung, Boanerges Putra; Blegur, Fried Allung; Klau, Anggelina Delviana (Asian Journal of Agriculture and Rural Development, 2023)
The Indonesian government has created a food estate area in Belu Regency, supported by the construction of the Rotiklot Dam, in the expectation that it would increase agricultural production and income, as well as stimulate the economy of the border region. The study aims to analyze (i) the comparative advantage of agricultural commodities in the food estate area and (ii) the effect of social characteristics and physical inputs on increasing farmers’ production and income in the food estate area in the border region. The data used consisted of primary data obtained from interviews with 300 respondents, selected through purposive sampling from a population of 4500, and secondary data from related agencies. The data analysis employed location quotient (LQ) and the partial least squares approach to structural equation modeling (SEM-PLS). Social input was reflected by 5 variables and physical input by 3 variables, while production was reflected by 6 variables and income by 7 variables. The LQ results show that maize and rice production in the food estate area is superior to other areas, and maize grows faster than rice crops. The comparative advantage is due to physical and social factors; based on the results of SEM-PLS, physical factors have direct and indirect effects on production and income, while social factors have an indirect effect on farmers’ income through agricultural production. Expansion of the planting area by utilizing water from the Rotiklot Dam and increasing the motivation of farmers through input subsidies are needed to optimize the increase in farmers’ production and income.